Kristen Swanson's theory of care: literature review - Berstain-García, Isabel (Universidad de Sonora, 2022)
Introduction: Over the years, the nursing discipline has sought to base the interventions of its work by applying theories that are specific to this discipline, such as the theory of care, which provides the guideline to transfer it to the areas of action. Objective: Analyze the scientific evidence available on the application of Kristen Swanson's theory of care in nursing practice. Methodology: The Cooper's methodology was used in order to review literature regarding the theory of care; different databases were consulted: IMBIOMED, CUIDEN, ScienceDirect, Fundación Index, MEDLINE, ciberINDEX, SciELO, Redalyc, among others. The descriptors used were: nursing, nursing care, nursing theory, in Spanish, English and Portuguese between the years 2015 and 2019; all types of literature were included, obtaining a sample of 42 papers and dissertations. Results: Most of the documents assessed do not fully capture the basic processes of care proposed by Swanson. The theory has proven to be useful in the area of care, development of intervention programs with neonates, post-operative cardiopediatric patients, breastfeeding, puerperium care and modification of attitudes towards organ donation. Conclusion: The theory is considered essential for integral assessment, and adopting its foundations and concepts is of great utility, since it favors the generation of a first learning space; moreover, it is useful to provide accompaniment to the patient and his family, and to offer them strategies for improvement. More intervention, qualitative and teaching research is required.